Perilaku Biaya : Analisis Komparatif Melalui Pendekatan Teoritis dan Praktik Pada Biaya Tetap - Anisa Rahmawati; Annatasia Adinda Carina; Frisa Ayudi Putri; Jean Tyoma Uli Tasya S; Zitha Alifia Ramadhana (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to provide an explanation related to the basic concepts in the development of cost behavior, which is viewed from theoretical and practical cost behavior. The aim of writing this article is to provide a comprehensive picture of cost behavior towards fixed costs. It is hoped that the results of this research can be used by management in estimating more accurate production costs. For academics, this paper is useful for increasing insight and bringing theoretical concepts closer to a practical level. This research reviews the nature of cost behavior by examining the relationship between total costs and changes in cost drivers, which exist in manufacturing companies. Based on the discussion in this research, basically the nature of cost behavior can be grouped into two, namely fixed and variable. Fixed costs have the characteristic that the total costs remain the same, even though the cost drivers change. Meanwhile, variable costs are characterized by total costs that change proportionally to changes in the cost driver.